Intra-stock diversity in egg specific gravity of Atlantic cod in Icelandic waters - Lovísa Ólöf Guðmundsdóttir 1986- (2013)
The specific gravity of fish eggs affects their vertical distribution in the water column and thus their transportation routes and survival. Previous studies have shown that egg specific gravity can be adapted to the local conditions, for instance to reduce the chances of unsuitable drift routes or to avoid hostile conditions for development. The Icelandic cod stock has been shown to consist of two distinct behavioural types, usually referred to as frontal or coastal fish that occupy the same spawning grounds but exhibit either deep-water or shallow-water migration behaviour outside the spawning periods. The main objective of this study was to compare the egg specific gravity of the two behaviour types of cod found in Icelandic waters and see if it contributes to the maintenance of the two groups. Eggs were collected and fertilized in vitro from spawning grounds southwest of Iceland in April 2010 and 2011. Egg specific gravity obtained from days 2, 3 and 4 after fertilization showed no difference between the behaviour groups while there were strong indications of the eggs of frontal cod being lighter than the eggs of coastal cod during the last stages of development. Egg diameter was also found to vary between the two groups as frontal cod produced larger eggs than coastal cod. These results reveal previously unknown differences in the life-history of the two behaviour groups and might be attributed to environmental factors or genetics. Eðlisþyngd fiskeggja hefur áhrif á lóðrétta dreifingu þeirra í sjónum og þar af leiðandi dreifingu þeirra með mismunandi straumum og hugsanlega afkomu. Fyrri rannsóknir hafa sýnt að eðlisþyngd fiskeggja getur verið aðlöguð að umhverfisaðstæðum, til dæmis til að draga úr líkum á óhentugu reki eða til að forðast óhagstæðar aðstæður fyrir þroskun. Sýnt hefur verið fram á að íslenski þorskstofninn er samsettur úr tveimur aðgreindum atferlisgerðum sem nota þó sama hrygningarsvæði. Þessar gerðir eru yfirleitt kallaðar grunnfars- og djúpfarsþorskar og byggist aðgreining á atferli ...